PENGARUH STRESSOR TERHADAP PRESTASI KERJA MELALUI STRESS KERJA KARYAWAN PTPN XII KEBUN NGRANGKAH PAWON KEDIRI - Diah Kusumawati (Manajemen Bisnis, 2013)
Diah KusumawatiProgram Studi Manajemn FEB UMME-mail: diahkusuma@yahoo.co.idABSTRACTThe purpose of this study were (1) to determine the stressors, (2) to know the job stress level (3) tofind out the level of work performance and (4) whether the stressor effect on the employee stress atPTPN XII Kebun Ngrangkah Pawon Kediri. Analysis tool used to determine the stressors and stressthat and to determine the level of employee performance was range-scale analysis. To know theeffect of stressor on the job stress and its impact on employee performance was used path analysismodel. The results of the analysis indicate that stressor and stress were in high level category. Thelevel of employee performance was also in high category. The results of path analysis show that wasa significant effect between a stressor to employee’s job stress, there was also a significant effectbetween the job-stress to employees’ performance. It mean that there was a significant effect betweenstressors to performance level through job stress. Based on the results, it could be suggested that thelevel of work stressors and job stress should be reduced. Giving reward would be better applied forbetter working employees, so it could motivate employees enthusiastic in their work.Keywords: Stressor, Job Stress and Job Performance